2020
DOI: 10.1101/2020.02.13.947952
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Neural Basis for a Persistent Internal State inDrosophilaFemales

Abstract: Sustained changes in mood or action require persistent changes in neural activity, but it has been difficult to identify and characterize the neural circuit mechanisms that underlie persistent activity and contribute to long-lasting changes in behavior. Here, we focus on changes in the behavioral state of Drosophila females that persist for minutes following optogenetic activation of a single class of central brain neurons termed pC1. We find that female pC1 neurons drive a variety of persistent behaviors in t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 103 publications
1
9
0
Order By: Relevance
“…2), we could then determine all synaptic connections (via automated synapses (Buhmann et al, 2019)) between these neurons and earlier neurons in the pathway. We also examined connections to higher-order neurons shown to be pulse-preferring (vpoEN (Wang et al) and pC2l (Deutsch et al, 2019)), to drive a persistent internal state in females (pC1d/e (Deutsch et al, 2020)), and descending neurons that drive song-responsive behaviors (pMN1/DNp13 (Wang et al) and pMN2/vpoDN (Deutsch et al, 2019; Wang et al, 2020b)) (Fig. 9A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2), we could then determine all synaptic connections (via automated synapses (Buhmann et al, 2019)) between these neurons and earlier neurons in the pathway. We also examined connections to higher-order neurons shown to be pulse-preferring (vpoEN (Wang et al) and pC2l (Deutsch et al, 2019)), to drive a persistent internal state in females (pC1d/e (Deutsch et al, 2020)), and descending neurons that drive song-responsive behaviors (pMN1/DNp13 (Wang et al) and pMN2/vpoDN (Deutsch et al, 2019; Wang et al, 2020b)) (Fig. 9A).…”
Section: Resultsmentioning
confidence: 99%
“…We used FAFB reconstructions corresponding to previously known auditory neurons (Dorkenwald et al 2020), higher-order auditory neurons (Deutsch et al, 2020; Wang et al, 2020b), and all auditory WED/VLP neurons for which we found EM reconstructions. We then found all automatically detected synapses between every pair of individual neurons (Buhmann et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The five cell types that make up the pC1 group express dsx and have been implicated in female receptivity, oviposition, male courtship, and both male and female aggression (Deutsch et al 2020;Fathy, 2016;Hoopfer et al, 2015;Ishii et al, 2020;Koganezawa et al, 2016;Palavicino-Maggio et al, 2019;Rideout et al, 2010;Wang et al, 2020a,b;Wohl et al, 2020;Zhou et al, 2014). In previous work, the lack of cell-type specific genetic reagents has made it difficult to elucidate the relative contribution of the five pC1 cell types in females to each of these behaviors.…”
Section: Aipg and Pc1d Are Two Key Groups Of Neurons Involved In Femamentioning
confidence: 99%
“…A complementary study by Deutsch et al (2020) found that combined activation of pC1d and pC1e using ReaChR resulted in a persistent phenotype lasting for minutes. Using lines labeling aIPg cells, we did observe head butting and fencing behaviors after the cessation of the optogenetic stimulus that lasted for a shorter, but ethologically relevant (Bath et al, 2017;Yuan et al, 2014), time period on the order of 10s of seconds.…”
Section: Involvement Of Pc1d In Female Aggression and Connections Tomentioning
confidence: 99%
See 1 more Smart Citation